2009
DOI: 10.1111/j.1540-8183.2009.00477.x
|View full text |Cite
|
Sign up to set email alerts
|

Culprit‐Only or Multivessel Percutaneous Coronary Stenting in Patients with Non‐ST‐Segment Elevation Acute Coronary Syndromes: One‐Year Follow‐Up

Abstract: Multivessel stenting in patients with NSTE-ACS and multivessel disease using a clinical decision of treatment is associated with lower rate of MACE driven by lower repeat revascularization, compared with culprit-vessel stenting, without difference in rates of death or MI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
1
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 19 publications
2
29
1
3
Order By: Relevance
“…These results were agreed with the present study. In agreement with our study, Zapata et al [14] investigated the major cardiac events at 1-year follow-up of multi-vessel versus culprit-vessel stenting in patients presenting with NSTE-ACS and multi-vessel disease (MVD). The incidence of MACE was lower in MVR (9.45% vs. 16.34%, P = 0.02) with lower revascularization rate (7.46% vs. 13.86%, P = 0.04) than in CVR.…”
Section: Discussionsupporting
confidence: 60%
“…These results were agreed with the present study. In agreement with our study, Zapata et al [14] investigated the major cardiac events at 1-year follow-up of multi-vessel versus culprit-vessel stenting in patients presenting with NSTE-ACS and multi-vessel disease (MVD). The incidence of MACE was lower in MVR (9.45% vs. 16.34%, P = 0.02) with lower revascularization rate (7.46% vs. 13.86%, P = 0.04) than in CVR.…”
Section: Discussionsupporting
confidence: 60%
“…6 However, few studies have compared outcomes of MVR and SVR in these patients undergoing PCI. 7,8,12 Results from previous studies are controversial. Moreover, these studies were conducted before the introduction of DES and cannot reflect current practice.…”
Section: Discussionmentioning
confidence: 99%
“…These results were consistent with the results from previous studies with bare-metal stents on the same topic. 7,8 Because selection of treatment strategy is apt to be strongly affected by jeopardized myocardial territory and lesion complexity, we investigated whether the benefit of MVR might differ according to the APPROACH lesion score and the SYNTAX score. Although the SYNTAX score did not affect treatment strategy, the APPROACH lesion score was associated with the performance of MVR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Several observational single-center studies have also reported lower rates of MACE in patients with NSTEACS and multivessel disease who underwent CR with drug-eluting stents compared with culprit lesion revascularization only. 22,23 However, none of these studies were randomized, and it is possible that residual confounding (eg, the extent of atherosclerosis) explains the worse prognosis in patients with ICR. Treating additional nonculprit lesions in ACS to achieve CR would likely entail some excess risk of procedural complications and additional cost.…”
Section: Clinical Implications and Future Directionsmentioning
confidence: 99%